A plant secretory sequence enhances immunogenicity of electroporated COVID-19 DNA vaccines - Demurtas, Olivia Costantina; Novelli, Flavia; Triggiani, Doriana; Merla, Caterina; Pasquali, Emanuela; Massa, Silvia; Franconi, Rosella; Pioli, Claudio (Frontiers in Medical Technology, 2025)
IntroductionAs paradigmatically shown by SARS-CoV-2 vaccines, nucleic acids-based vaccines represent powerful tools to rapidly tackle fast emerging pathogens limiting their spread in human populations and/or reducing the health impact in affected patients. Compared with RNA vaccines, DNA vaccines offer higher stability and amenability to fast development due to tailor-made design of several candidates at a time for (pre)clinical settings. However, their scarce immunogenicity represents an important drawback, requiring technological strategies to enhance cellular uptake, protein expression and increase the ability to induce an immune response.MethodsWe investigated the effects of combining a plant secretory signal sequence of the PolyGalacturonase-Inhibiting Protein (PGIP) from Phaseolus vulgaris with electro-gene transfer (EGT), a technology that increases DNA delivery, on the immune response induced by different SARS-CoV2 experimental DNA vaccines based on domains and peptides of the spike (S), membrane (M) and nucleocapsid (N) proteins.Results and discussionAll the DNA constructs resulted in protein expression in vitro and in the induction of both antibody and CD4 and CD8T cell responses in mice. EGT significantly increased DNA constructs immunogenicity, especially for the induction of antibody response, confirming its potential in DNA vaccination. Remarkably, constructs including the plant secretory signal sequence resulted to be highly expressed and triggered higher antibody and CD4T cell responses, highlighting that the combination of this sequence and EGT can be used to boost the immunogenicity of DNA-vaccine coded proteins, ultimately helping in their design.